Gastronomic ethnobotany of traditional vegetables among the Sundanese in rural West Java, Indonesia - BUDIAWATI S. ISKANDAR; BUDI IRAWAN; DEDE MULYANTO; JOHAN ISKANDAR; AFDILAH AFINANDA; BUDI RAJAB (Society for Indonesian Biodiversity, 2023)
Abstract. Iskandar BS, Irawan B, Mulyanto D, Iskandar J, Afinanda A, Rajab B. 2023. Gastronomic ethnobotany of traditional vegetables among the Sundanese in rural West Java, Indonesia. Biodiversitas 24: 3932-3950. Sundanese people in West Java have been known for their tradition of consuming various vegetable plants (Lalab). This study aims to elucidate the Traditional Ecological Knowledge (TEK) on various vegetable plants, folk classification, and use and processing of vegetable plants for family use in the rural Sundanese community in Cijambu Village, Tanjungsari Sub-district, Sumedang District, West Java, Indonesia. This study employed mixed qualitative and quantitative methods with an ethnobotanical and gastronomic approach. The results showed that 67 different local varieties (landraces) of vegetable plants were documented from 65 species, representing 56 genera and 27 families that the Sundanese people of Cijambu commonly use. These vegetable plants can be classified into three categories: vegetable source, part used, and use and processing of vegetables. The people obtain their vegetables from various sources, such as their homegardens, gardens, rice fields, Perhutani agroforests, and other non-farming sources, including markets, small village shops, and vegetable sellers. The parts of vegetable plants usually consumed by the people of Cijambu Village can be divided into eight parts: the bulb, flower, fruit, leaf, rhizome, root/tuber, seed, and shoot. The vegetable plants are traditionally consumed as fresh raw salad and cooked vegetables, spices, and at least 12 main or basic types of Sundanese food meals, namely various Acar, Asinan, Buntil, Karedok, Lodeh, Lotek, Rujak, Sambel, Sayur/Angeun, Semur, Tumis/Oseng, and Urab with a total of 58 kinds of food meals. At the same time, various Sundanese chili sauces (Sambel) were documented in at least 14 types. Based on ethnobotanical gastronomy, the Sundanese community's cultural practice of consuming Lalab results from a complex interaction between human communities, food, and their local environment.